Transcription of biochemical defenses by the harmful brown tide pelagophyte, Aureococcus anophagefferens, in response to the protozoan grazer, Oxyrrhis marina - Dawydiak, Walter; Gobler, Christopher J. (Frontiers in Microbiology, 2023)
Aureococcus anophagefferens (Hargraves et Sieburth, 1988) is a small marine pelagophyte that forms recurrent harmful brown tides blooms with adverse ecological and economic impacts. During blooms, A. anophagefferens experiences lower zooplankton grazing mortality than other phytoplankton potentially due to the synthesis of anti-predator compounds including extracellular polysaccharides. This study characterized the transcriptomic response of A. anophagefferens to the protozooplankton, Oxyrrhis marina, and assessed whether this response involved chemical cues. Transcriptomes were generated from A. anophagefferens populations grown at high (1x106 cells mL-1) and low (5x105 cells mL-1) cell densities incubated directly with O. marina or receiving only filtrate from co-cultures of A. anophagefferens and O. marina to evaluate the role of chemical cues. There were a greater number of genes differentially expressed in response to grazing on the lower concentration of A. anophagefferens compared to the high concentration treatment and in response to direct grazing compared to filtrate. KEGG pathway analysis revealed that direct grazer exposure led to a significant increase in transcripts of genes encoding secondary metabolite production (p<0.001). There was broad transcriptional evidence indicating the induction of biosynthetic pathways for polyketides and sterols in response to zooplankton grazers, compounds associated with damage to marine organisms. In addition, exposure to O. marina elicited changes in the abundance of transcripts associated with carbohydrate metabolism that could support the formation of an extracellular polysaccharide matrix including genes related to glycoprotein synthesis and carbohydrate transport. Collectively, these findings support the hypothesis that A. anophagefferens can induce biochemical pathways that reduce grazing mortality and support blooms.